Swine Pasteurellosis A disease of concern to Pig Industry - Verma, Harshit; Rawat, Mayank; Verma, Rishendra (Indian Farming, 2015)
Septic pasteurellosis caused by a Gram negative cocobacillus bacteria P. multocida causes outbreaks leading to quite fairly high mortality and morbidity. The onset of the disease is sudden and its course is brief extending from few hours to 2 to 3 days. Affected animals show signs of dullness, anorexia, cough, high temperatures, swelling of pharyngeal region, diffuse bluish red discoloration of the skin, particularly around the ears, neck, flanks, snout and under the abdomen, dyspnoea, incoordinating gait and prostration and death within 24 to 36 hours in a high percentage of cases. In very young pigs, death may occur in 12 hours. A differential diagnosis should be made to exclude disease like salmonellosis and swine fever virus wherein similar type of clinical signs are seen. Till the development of pig strain based pasteurellosis vaccine, conventional vaccine may be used in sows. The farm management should enforce stringent biosecurity measures.